Advancements in Hydrogel-Based Adsorbents for Heavy Metal Removal: An Overview - S. Neama, Hadeel; H. Alwash, Atheel; Ali, Mutaz; Gholami, Fatemeh; Gholami, Zahra (Al-Nahrain Journal of Science, 2024)
The environment and public health face a significant risk from increasing levels of heavy metals in wastewater resulting from industrial activities. Researchers are exploring new techniques for eliminating these pollutants by the production of potential hydrogel materials that can provide a comprehensive analysis of recent advancements in the utilization of these hydrogels for the adsorption of heavy metals from aqueous solutions. Heavy metal pollution poses a significant threat to ecosystems and human health, necessitating effective remediation strategies. Hydrogels, with their unique physicochemical properties, have emerged as promising materials for heavy metal adsorption due to their high-water retention capacity, tunable porosity, and the active functional groups. This review discusses the significance of hydrogels as effective adsorbents for removing heavy metals and the impact of reaction conditions on their adsorption efficiency. Furthermore, it explores the principles of adsorption mechanisms involved, such as ion exchange, chelation, and electrostatic interactions, which are critically evaluated in terms of adsorption capacity, selectivity, and recovery.